The Republic of Korea’s experience with an ocean dumping management system to enhance compliance with the London Protocol: highlights of major institutional history over 40 years - Kim, Chang-Joon; Chung, Chang Soo; Shin, Kyung-Hoon; Choi, Ki-Young (Frontiers in Marine Science, 2023)
Since the late 1980s, in efforts to reduce the burden of waste treatment on land and to protect the nation’s rivers, the Korean government has licensed dumping at sea only for waste difficult to treat on land. However, owing to the “not in my backyard” (NIMBY) phenomenon and the higher cost of land-based treatment, the amount of ocean-dumped waste has increased rapidly. The categories of waste dumped have also expanded to include sewage sludge containing highly concentrated hazardous substances, raising concerns about damage to the marine environment. The Korean Ministry of Oceans and Fisheries has noted that compliance with the London Protocol could be essential for limiting ocean dumping activities. The Republic of Korea enacted comprehensive measures to ensure compliance and formally acceded to the London Protocol in 2009. This paper presents Korea’s implementation of the criteria that led to the cessation of ocean dumping of sewage sludge in 2016.